The Use of Active Reading Strategy to Improve Students’ Reading Comprehension at Tenth Grade of SMA Negeri 7 Padangsidimpuan - Meliana Sari; Mahrani; Tambunan, Elissa Evawani (Yayasan Perguruan Kampus, 2025)
The aim of this research study is to determine the students’ reading comprehension through the Active Reading strategy in English text. The fact showed that students have low skill of reading comprehension based on the mean score 65 while the Minimum Criterion Succes was 75. This gap become a reason that formulate the problems as, How the students’ reading comprehension improvement by using Active Reading strategy?. This research conducted under quantitative research method of Class Action research (CAR) design with the number of students are 32 from tenth grade of SMA Negeri 7 Padangsidimpuan. The written test are used to collect the data and analyzed based on statistical formula. The research finding showed that in pre test the students’ reading comprehension mean score was 44.3 then after applied Active Reading strategy the mean score in post-test cycle 1 was 71 and in post-test cycle 2 was 82.9. The students’ improvement from pre-test to post-test cycle 2 was 86.8%. It means that there was a significant improvement of students’ reading comprehension by using Active Reading strategy in reading English text. This finding was recommended to be applied in teaching and learning process of reading toward English text.